UV-C Light: A Promising Preservation Technology for Vegetable-Based Nonsolid Food Products - Rose Daphnee Tchonkouang; Alexandre R. Lima; Andreia C. Quintino; Nathana L. Cristofoli; Margarida C. Vieira (Foods, 2023)
A variety of bioactive substances present in fruit- and vegetable-processed products have health-promoting properties. The consumption of nutrient-rich plant-based products is essential to address undernutrition and micronutrient deficiencies. Preservation is paramount in manufacturing plant-based nonsolid foods such as juices, purees, and sauces. Thermal processing has been widely used to preserve fruit- and vegetable-based products by reducing enzymatic and microbial activities, thereby ensuring safety and prolonged shelf life. However, the nutritional value of products is compromised due to the deleterious effects of thermal treatments on essential nutrients and bioactive compounds. To prevent the loss of nutrients associated with thermal treatment, alternative technologies are being researched extensively. In studies conducted on nonsolid food, UV-C treatment has been proven to preserve quality and minimize nutrient degradation. This review compiles information on the use of UV-C technology in preserving the nutritional attributes of nonsolid foods derived from fruit and vegetables. The legislation, market potential, consumer acceptance, and limitations of UV-C are reviewed.